Three-dimensional Discrete Element Method simulation system of the interaction between irregular structure wheel and lunar soil simulant. (October 2020) - Zhang, Rui; Pang, Hao; Dong, Wenchao; Li, Tao; Liu, Fang; Zhang, Hua; Hu, Zhenyu; Li, Jianqiao
Highlights: Based on the theory of terramechanics, the 3D dynamic simulation system was established by combining CATIA and PFC3D. The rationality of the simulation system was verified by the wheel soil-bin test. In addition to the flat surface of ground, two kinds of lunar environments simulant were added to the simulation system. The distribution of lunar soil stimulant can be observed more clearly by the changes of color gradients and the post-processing of IV program. Abstract: The experimental execution, theoretical analysis, structural optimization and performance prediction of lunar rover wheels are subject to many limitations due to the particularity and complexity of the lunar environment. The numerical simulation has notable advantages in analyzing the interaction between wheels and lunar soil simulant and designing the lunar rover wheels applied to complex environments. In this paper, based on the theory of terramechanics, a three-dimensional (3D) dynamic system that simulated the interaction between irregular structure wheels and lunar soil simulant was established using the interface code and embedded FISH language of PFC3D. The rationality of the simulation system was verified by the wheel soil-bin test. Then, in order to improve and optimize the 3D dynamic simulation system, the interaction between wheel and lunar soil simulant was simulated in two different kinds of simulated lunar environments besides the flat ground, and the climbing property of the wheel was analyzed qualitatively. Finally, the mesoscopic changes of lunar soil stimulant particles were characterized by the color gradient variations, and the simulation results were processed in the IV program so that the distribution of lunar soil stimulant particles under the wheel could be observed more clearly. This research provided a reliable method for the study of the interaction between irregular wheel and loose lunar soil in complex environments and of designing the wheel structure.